5x-2^+36>5x5x-33x4x+2+40 больше или равно 4x3x+7-4

(5x-2)^+36>5x(5x-3)
3x(4x+2)+40 больше или равно 4x(3x+7)-4

    -25x^2-10x>-32

     

    x=36/22=18/11

    -22x>=-36

    25x^2+10x-32=0

    12x^2-12x^2+6x-28x>=-40+4

    12x^2+6x+40>=12x^2+28x-4

    -25x^2+25x-15x>4-36

    25x-4+36>25x^2-15x

    D=10^2-4*25*(-32)=100+3200=3300

    x2=-10-3300/50=66,2

    x1=-10+3300/50=65,8

    x1,2=-10+-3300/50

  • (5x-2)^+36>5x(5x-3)

     

    -25x^2-10x+32>0 |:(-1)

     3x(4x+2)+40>= 4x(3x+7)-4